Xanthomatous meningioma: A metaplastic or degenerative phenomenon?. Issue 6 (5th September 2018) - Wong, Yin Ping; Tan, Geok Chin; Kumar, Ramesh
Abstract : Xanthomatous changes can be observed in various conditions including primary xanthomatosis that is linked to an underlying hypercholesterolemia and more commonly associated with secondary xanthomatous degenerative processes in neoplasm and chronic inflammation. Meningioma with extensive xanthomatous change is exceedingly rare. The presence of cholesterol clefts within this peculiar meningioma subtype has not been described. Herein, we report an unusual case of xanthomatous meningioma in an 83‐year‐old normolipidemic woman, who presented to us with worsening lower limb weakness and global aphasia. There was increasing evidence to suggest that the presence of xanthomatous changes in long‐standing meningioma is merely a sequela of cellular degeneration rather than true metaplastic change as previously hypothesized. Hence, the diagnosis of "xanthomatous meningioma" in the metaplastic category should be revisited and considered as a distinct histological subtype. The possible histogenesis of such intriguing phenomenon is discussed with a review of the literature.